Peran Ibu dalam Perkembangan Psikologi Anak - Eti Shobariyah (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2019)
The development of a child's psychology is a series of physical and spiritual changes of the child toward a more advanced and perfect direction. However, it is also necessary for the writer to suggest that some people consider development as a different process from growth. The development is not the same as growing and vice versa. The development of a child's psychology is the changes experienced by the child to the level of maturity or maturity (maturation) that takes place systematically, progressively, and continuously, both in terms of physical (physical) and psychological (spiritual). The whole process of child development is regulated and controlled by the power of social law that occurs because of the associated elements so that what was originally simple (a few elements) is increasingly complex and more numerous. One of the social environments that influence the child's development is the family, in this case, the mother, because the mother is the first person to instill characteristics in the child so that what is done and said by the mother is what will be done by a child. In this case, a mother plays an important role and influences the psychological development of children since the child is in her mother's womb. Motherly tasks are the most honorable jobs and require skills in this world. The implementation of this task is very important for the care and protection of children, especially in the early stages of growth.